SOYBEAN AND ITS ADAPTIVE PROPERTIES AS A WAY TO SOLVE THE GLOBAL FOOD CRISIS - Kobyrenko, Yu.; Panasiuk, R.; Sydorak, I.; Vavrynovych, O. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
Today, the global food crisis is becoming increasingly severe. Food production is unable to meet the needs of the growing population of the planet. As a result, some countries are experiencing a severe lack of basic food. This issue is further exacerbated by rapid climate change, which negatively impacts food production and reduces its volume. More and more attention is paid to legumes, in particular soybeans, as plants that have a balanced protein composition and can be a key link in the fight against the world food crisis. It has been shown that soybeans are currently the largest legume crop in Ukraine by area and are grown as one of the main crops because they combine economic, agronomic, and environmental components. The climatic conditions and soil composition in all regions of Ukraine are favorable for the successful cultivation of the crop and high yields. However, regardless of this, global warming harms the entire planet, and Ukraine as well. This also applies to other European countries. The main task of breeders today is to create varieties of a new generation that will be stress-resistant under new, radically different conditions of existence, and at the same time give high yields. Therefore, it is interesting and experimental to study the adaptive properties of soybeans by sowing it in atypical conditions of existence. In the course of research, the researchers will observe all the ontogenesis processes of Ukrainian soybean varieties in Spain, and Spanish varieties in Ukraine. Under contrasting conditions of existence (temperature indicators, humidity, soil composition and structure), it is possible to observe the plasticity of these soybean varieties and their stress resistance. The experiment will also enable the investigation of nitrogen fixation of these soybean varieties in different countries with different conditions of existence, as well as nitrogen fixation of these soybean varieties in different countries with different living conditions. This natural biologization is a unique phenomenon and requires detailed study, especially now, at a time of rapid climate change.